The Role of Small and Medium Enterprises in Supporting a Nation's Economy - Manoharan, Vishnupriyanga (Economics and Business International Conference Proceeding, 2024)
Reviewing previous research on the contribution of small and medium-sized businesses (SMEs) to a nation's economy is the goal of this study. This study uses a literature review methodology to determine the elements that affect SMEs' contributions to economic growth, such as innovation, job creation, wealth distribution, and poverty reduction.In order to comprehend the extent of SMEs' contribution to economic stability, the evaluated literature includes a variety of theoretical stances and prior research findings from diverse nations. By contributing significantly to GDP, opening up business opportunities, and improving economic inclusion through fair access to resources, SMEs strategically assist economic development, according to the analysis's findings. However, barriers including a lack of funding, restricted access to technology, and unhelpful government regulations frequently impede the growth of SMEs.In order for SMEs to contribute as much as possible to the expansion of the national economy, this assessment suggests that pro-SME policies, assistance from a range of stakeholders, and enhanced access to financing and technology are crucial.